Effect of erbium, chromium-doped: yttrium, scandium, gallium, and garnet laser-assisted periodontal therapy using radial firing tip during early healing period: a randomized controlled split-mouth clinical trial - Jung Soo Park; Hannah Jung; Jae-Jun Ryu; Ki-Tae Koo; Jaebum Lee (BMC, 2024)
Abstract Background This study aimed to demonstrate the efficacy of erbium, chromium-doped:yttrium, scandium, gallium, and garnet (Er,Cr:YSGG) laser-assisted nonsurgical periodontal therapy in periodontitis patients during 8 weeks of healing. Methods A split-mouth, single-blinded, randomized controlled clinical trial was conducted on 12 patients diagnosed with stage III/IV periodontitis and had a minimum of two teeth with probing pocket depth (PPD) > 5 mm in at least two quadrants. Upon randomization, each quadrant was assigned for conventional scaling and root planing (SRP) procedure or laser-assisted therapy (SRP + laser) using radial firing tip (RFPT 5, Biolase). Clinical measurements and gingival crevicular fluid collection were performed for statistical analysis. Results In the initial statistical analysis on the whole subject teeth, modified gingival index (MGI) reduction was greater in test group at 1(P = 0.0153), 4 (P = 0.0318), and 8 weeks (P = 0.0047) compared to the control in the same period. PPD reduction at 4 weeks in test group was -1.67 ± 0.59 showing significant difference compared to the control (-1.37 ± 0.63, P = 0.0253). When teeth with mean PPD ≥5 mm were sorted, MGI decrease was significantly greater in test group at 1 (P=0.003) and 8 week (P=0.0102) follow-ups. PPD reduction was also significantly greater in test group at 4 week period (-1.98 ± 0.55 vs -1.58 ± 0.56, test vs control, P=0.0224). Conclusions Er,Cr:YSGG-assisted periodontal therapy is beneficial in MGI and PPD reductions during early healing period.